The everyday lives of sovereignty political imagination beyond the state - Bryant, Rebecca; Reeves, Madeleine (Cornell University Press, 2021)
"This book addresses popular assertions of sovereignty and projects of sovereign agency with particular reference to areas of disputed territory in contemporary Europe, Asia, North Africa and the Middle East"--
2106
Keywords: Staat; Souveränität; Politische Anthropologie; Sovereignty; Aufsatzsammlung; Konferenzschrift -- 2015 -- Nikosia